Privileges of domestic servants: a one paid day off within a week proposal for domestic servants / Nur Hidayah Mhd Mustaffa … [et al.] - Mhd Mustaffa, Nur Hidayah; Mohd Nazer, Filya Naziera; Pandang, Emma Kati; Radzuan, Fatin Hakimah; Robinson, Rozy Tijan (Faculty of Law, 2010)
For decades, there have been numerous cases between domestic servants and the employers such as poor performance of the domestic servant and the severe cases where the employers abused the domestic servants. In Malaysia, various organizations such as TENAGANITA and Malaysia Trade Union Congress suggested that the government should implement a one paid off day weekly for domestic servants. Essentially, domestic servants are not recognized as workers and they do not enjoy the privileges and protections. Recently, the Malaysia government had announced that they intend to implement a weekly day off for domestic servants as compulsory. There are several interviews which have been completed to obtain this information. The target groups of interviewees chosen were the Ministry of Human Resource, the Deputy Director of Immigrant Sector of Immigration of Malaysia, the Commissioner of Human Rights Commission of Malaysia and the Program Director of TENAGANITA Sdn. Bhd. In this research, we may see that there are more advantages towards the domestic servants and employers when a one day off for domestic servants implemented.